Differential Gene Expression and Pathway Analysis in Juvenile Nasopharyngeal Angiofibroma Using RNA Sequencing. (September 2018) - Jones, Joel W.; Usman, Shireen; New, Jacob; Holcomb, Andrew; Gunewardena, Sumedha; Tawfik, Ossama; Hoover, Larry; Bruegger, Daniel; Thomas, Sufi Mary
Juvenile nasopharyngeal angiofibroma (JNA) is a highly vascularized and locally aggressive tumor that typically presents in adolescent males. The molecular biology of this tumor remains understudied. We sought to identify differentially expressed genes in the JNA transcriptome through messenger RNA sequencing of primary fibroblasts from 2 tumor explants and tonsil tissue from tumor-free subjects. In total, 1088 significant, differentially expressed genes were identified with 749 upregulated and 339 downregulated. Pathway analysis identified a number of activated signaling pathways, most notably, the vascular endothelial growth factor (VEGF) pathway (adjusted overlap P = .03). VEGF-A showed a 4.4-fold upregulation in JNA samples. In addition, the angiogenic receptor, fibroblast growth factor receptor 2 (FGFR2), was not present in tumor-free samples but increased in JNA. We validate these findings with immunohistochemistry, demonstrating upregulation of VEGF and FGFR2 in patient sections. Inhibition of the VEGF or FGFR signaling axes may have therapeutic potential in the treatment of JNA.